An Investigation into the Self-Handicapping Behaviors in Terms of Academic Procrastination - Fadhli, Muhammad; Sudirman, Subhan Ajrin; Kılınçer, Hatice (International Journal of Islamic Educational Psychology, 2021)
Academic procrastination in completing tasks often occurs in students. If left unchecked, it will affect emotional instability, attitudes, and daily behavior. One of the reasons behind it is the threat of self-esteem and self-image. Among the individual attitudes of emotional evasion and threatening self-esteem and self-image is self-handicapping. This study aims to determine the relationship between self-handicapping and academic procrastination in UIN Imam Bonjol Padang students. The research instrument used a self-handicapping scale and an academic procrastination scale. Data were analyzed using the Pearson correlation analysis technique. The results showed a significant number of 0.234 (p>0.05), meaning no relationship between self-handicapping and academic procrastination in UIN Imam Bonjol Padang students.